Coffee consumption and cancer risk: a Mendelian randomisation study. Issue 10 (October 2022) - Carter, Paul; Yuan, Shuai; Kar, Siddhartha; Vithayathil, Mathew; Mason, Amy M.; Burgess, Stephen; Larsson, Susanna C.
Abstract: Background: Coffee contains many bioactive chemicals and associations with cancer have been reported in observational studies. In this Mendelian randomisation (MR) study we investigated the causal associations of coffee consumption with a broad range of cancers. Materials and methods: Twelve independent genetic variants proxied coffee consumption. Genetically-predicted risk of any cancer (59, 647 cases) and 22 site-specific cancers was estimated in European-descent individuals in UK Biobank. Univariable and multivariable MR analyses were conducted. Results: Genetically-predicted coffee consumption was not associated with risk of any cancer in the main analysis (OR 1.05, 95% CI 0.98–1.14, p = 0.183) but was associated with an increased risk of digestive system cancer (OR 1.28, 95% CI 1.09–1.51, p = 0.003), driven by a strong association with oesophageal cancer (OR 2.79, 95% CI 1.73–4.50, p = 2.5×10 −5 ). This association was consistent after adjustment for genetically-predicted body mass index, smoking and alcohol consumption. There was no strong evidence supporting a causal relationship between genetically-predicted coffee consumption and the majority of cancers studied. However, genetically-predicted coffee consumption was associated with increased risk of multiple myeloma (OR 2.25, 95% CI 1.30–3.89, p = 0.004) and reduced ovarian cancer risk (OR 0.63, 95% CI 0.43–0.93, p = 0.020). Conclusions: This MR study provides strong support for a causal association of coffee consumption with oesophageal cancer, but not for the majority of cancer types, and the underlying mechanisms require investigation.